PELATIHAN DIVERSIFIKASI TOMAT MENJADI PRODUK OLAHAN SAUS TOMAT DI DESA MONTONG BAAN - Anjarwani , Sri Endang; Wiguna, Lalu Habib Satya; Roslinda, Roslinda; Yuniarti, Yuniarti (Universitas Mataram, 2023)
Montong Baan Village is one of 14 villages in Sikur District, East Lombok Regency, West Nusa Tenggara Province. This village is a division of East Suradadi Village, established on November 3, 1938. Most of the people in this village work as crops (tomatoes and chilies) farmers. However, the lack of awareness related to the processing of agricultural products makes the community only depend on the livelihoods of farmers, whereas if the agricultural products are processed, they can make a product with high selling value. Therefore, the purpose of the University of Mataram Thematic Desapreneur Community Service Program for the period December 2022 - February 2023 is to help people create businesses by utilizing tomatoes through outreach and training in making tomato sauce. The stages carried out during the training were mixing ingredients, cooking, packaging, and marketing. The results obtained from this tomato sauce making training are that the people in Montong Baan Village can produce tomato sauce products that have been packaged and labeled and are ready to be marketed. Apart from that, the training on making tomato sauce in Montong Baan Village will certainly open up business opportunities and improve the economy for the community.